Multibody constrained dynamics of deepwater Y-method installation system. (15th June 2023) - Ullah, Naeem; Duan, Menglan; Onuoha, Mac Darlington Uche; Syed, Asad; Sajid, Muhammad; Sun, Guomin; Li, Wenda
Abstract: Installation of subsea equipment in deep water is a difficult task that necessitates a precise and safe executional strategy to minimize mishaps that might result in loss of life and equipment damage. Installation of a multibody structure is accompanied with undesirable dynamic behaviour and system responses. Due to its interconnectedness and nonlinearity, modelling the multibody dynamic system (MBDS) is challenging and complicated. In this study, the constrained dynamics of a multibody system is achieved by applying techniques including two tugboats and a payload in the context of an offshore installation scenario with a sea depth more than 1500 m. Given the lifting and installation operations performed using two wire ropes and three bodies with six degrees of freedom (6 –DOF), respectively, the coupled equations of motion of a multibody system are computed using Embedding Techniques or velocity Transformation Techniques. The hydrodynamic force and the two-strand forces are reduced to linear forces, but the hydrostatic force and the mooring forces are considered as nonlinear external loads. Runge-Kutta Method of Fourth-Order is used to calculate the numerical solution to the MBDS's equations of motion. The presented theoretical model is validated by comparing it to a previously published numerical model; the findings of both models are in good agreement. The outcomes of the suggested theoretical model are compared to the OrcaFlex numerical simulation. The suggested theoretical model demonstrates more computational accuracy and numerical stability than OrcaFlex. The findings of this investigation will enhance the safety and stability of multibody structure installation in deep water. Highlights: A coupled 18-DOF multibody system of dual floating barges with payload is modeled. Velocity transformation technique for the numerical solution of the dynamic model. The presented theoretical model is compared with result of simulated OrcaFlex model. Y-method installation analysis of the cables' traction & payload in regular waves. The safe and stable installation of deepwater multibody structures is presented.